1017 CLINICAL AND HEMODYNAMIC CHARACTERISTICS ASSOCIATED WITH LATENT PULMONARY VASCULAR DISEASE IN HEART FAILURE WITH PRESERVED LEFT VENTRICULAR EJECTION FRACTION. (15th December 2022) - Caravita, Sergio; Baratto, Claudia; Filippo, Aurora; Soranna, Davide; Battista Perego, Giovanni; Muraru, Denisa; Badano, Luigi P; Parati, Gianfranco
Abstract: Background: Among patients with heart failure and a preserved left ventricular ejection fraction (HFpEF), a distinct hemodynamic phenotype has been recently described, with potential clinical implication, i.e. latent pulmonary vascular disease (PVD). HFpEF patients with latent PVD have been shown to have worse outcome after creation of an interatrial septal shunt. However, the pathophysiological significance of latent PVD in HFpEF has not been thoroughly investigated. Methods: We retrospectively analyzed our cohort of consecutive patients with HFpEF who have undergone a right heart catheterization at rest and during exercise between 2016 and 2020. HFpEF was defined based on a resting and/or exercise hemodynamics: pulmonary artery wedge pressure (PAWP) > 15 mmHg at rest; PAWP during exercise >= 25 mmHg; PAWP/cardiac output (CO) slope > 2 mmHg/L/min. Latent PVD was defined based on exercise pulmonary vascular resistance (PVR) > 1.74 WU. Results: Out of 199 exercise right heart catheterization, 86 patients had a hemodynamic diagnosis of HFpEF. Of these, 68 (79%) qualified as HFpEF without PVD (HFpEF-PVR-) and 16 (21%) qualified as latent PVD (HFpEF-PVR+). HFpEF-PVR+ were older, presented more frequently with diabetes mellitus or glucose intolerance, had higher H2 FPEF and HFA-PEFF scores, slightly lower LVEF, had more frequently a history of atrial fibrillation and had more frequently at tricuspid regurgitation ≥ moderate (p<0.05). HFpEF-PVR+ had more frequently high PVR (> 2 WU) also at rest (72% vs 10%, p<0.001). At rest and only in HFpEF-PVR+, PVR was directly associated with PaCO2 (R 2 =0.21), while at peak exercise PVR was inversely associated with PvO2 as well as with stroke volume index (R 2 =0.32 and 0.31, respectively). HFpEF-PVR+ presented with a lack of decrease in PVR during exercise, higher mPAP both at rest and during exercise (p<0.05) in spite of non-different mean PAWP, and lower CO increase during exercise (p<0.05) in spite of similar CO at rest (Figure). HFpEF-PVD presented more frequently with exercise-induced tall V waves in the right atrium (50% vs 16%, p=0.002), indicating severe tricuspid regurgitation. Conclusions: HFpEF-PVR+ is associated with peculiar clinical and hemodynamic characteristics, reflecting a more advanced and polycomorbid HFpEF profile, characterized by heightened pulmonary vascular reactivity and overt cardiac limitation to exercise.